Strategies for Achieving Healthy Energy Balance Among African Americans in the Mississippi Delta - Groesbeck P. Parham, MD; Isabel C. Scarinci, PhD (Centers for Disease Control and Prevention, 2007)
IntroductionLow-income African Americans who live in rural areas of the Deep South are particularly vulnerable to diseases associated with unhealthy energy imbalance. The Centers for Disease Control and Prevention (CDC) has suggested various physical activity strategies to achieve healthy energy balance. Our objective was to conduct formal, open-ended discussions with low-income African Americans in the Mississippi Delta to determine 1) their dietary habits and physical activity levels, 2) their attitudes toward CDC's suggested physical activity strategies, and 3) their suggestions on how to achieve CDC's strategies within their own environment. MethodsA qualitative method (focus groups) was used to conduct the study during 2005. Prestudy meetings were held with African American lay health workers to formulate a focus group topic guide, establish inclusion criteria for focus group participants, select meeting sites and times, and determine group segmentation guidelines. Focus groups were divided into two phases.ResultsAll discussions and focus group meetings were held in community centers within African American neighborhoods in the Mississippi Delta and were led by trained African American moderators. Phase I focus groups identified the following themes: overeating, low self-esteem, low income, lack of physical exercise, unhealthy methods of food preparation, a poor working definition of healthy energy balance, and superficial knowledge of strategies for achieving healthy energy balance. Phase 2 focus groups identified a preference for social support-based strategies for increasing physical activity levels. ConclusionEnergy balance strategies targeting low-income, rural African Americans in the Deep South may be more effective if they emphasize social interaction at the community and family levels and incorporate the concept of community volunteerism.